2008
DOI: 10.1590/s0100-46702008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Flow injection analysis of vancomycin

Abstract: A flow injection method for the quantitative analysis of vancomycin hydrochloride, C66H75Cl2N9O24.HCl (HVCM), based on the reaction with copper (II) ions, is presented. HVCM forms a lilac-blue complex with copper ions at pH≅4.5 in aqueous solutions, with maximum absorption at 555 nm. The detection limit was estimated to be about 8.5×10-5 mol L-1; the quantitation limit is about 2.5×10-4 mol L-1 and about 30 determinations can be performed in an hour. The accuracy of the method was tested through recovery proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A survey of literature revealed that few methods based on visible spectrophotometry for VHC [5,6,7] have been reports. Other methods include HPLC [8,9,10,11], Polarography [12], Capillary electrophoresis [13], Radioimmunoa-ssay [14], Fluorescence polarization immunoassay [15] and Flow injection analysis [16,17]. This paper describes the batch and flow injection methods for spectrophotometric determination of vancomycin hydrochloride (VHC) by the diazotization-coupling reaction between VHC and diazotized metoclopramide (DMCP) in the presence of sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature revealed that few methods based on visible spectrophotometry for VHC [5,6,7] have been reports. Other methods include HPLC [8,9,10,11], Polarography [12], Capillary electrophoresis [13], Radioimmunoa-ssay [14], Fluorescence polarization immunoassay [15] and Flow injection analysis [16,17]. This paper describes the batch and flow injection methods for spectrophotometric determination of vancomycin hydrochloride (VHC) by the diazotization-coupling reaction between VHC and diazotized metoclopramide (DMCP) in the presence of sodium hydroxide.…”
Section: Introductionmentioning
confidence: 99%